Multi-Agent Systems : 12th European Conference, EUMAS 2014, Prague, Czech Republic, December 18-19, 2014, Revised Selected Papers - Bulling, Nils.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2015)
This book constitutes the proceedings of the 12th European Conference on Multi-Agent Systems, EUMAS 2014, held in Prague, Czech Republic, in December 2014. The 21 full papers and 8 short papers presented in this volume were carefully reviewed and selected from 79 submissions. They are organized in topical sections named: agent-based models, trust and reputation; coordination, coalitions and teamwork; logic and formal approaches; theories in practice and real-world problems; decision making, conflicts and agreements.
Agent-Based Models, Trust and Reputation -- Ants in the OCEAN: Modulating Agents with Personality for Planning with Humans -- A Trust-Based Situation Awareness Model -- Angerona - A Flexible Multiagent Framework for Knowledge-Based Agents -- Affordance-Based Interaction Design for Agent-Based Simulation Models -- MORE: Merged Opinions Reputation Model -- Coordination, Coalitions and Teamwork -- Computing Coalitions in Multiagent Systems: A Contextual Reasoning Approach -- Comparison of Task-Allocation Algorithms in Frontier-Based Multi-robot Exploration -- Homecoming: A Multi-robot Exploration Method for Conjunct Environments with a Systematic Return Procedure -- Distributed Deliberation on Direct Help in Agent Teamwork -- Forming Coalitions in Self-interested Multi-agent Environments Through the Promotion of Fair and Cooperative Behaviour -- Auction-Based Dynamic Task Allocation for Foraging with a Cooperative Robot Team -- Logic and Formal Approaches -- Tableaux and Complexity Bounds for a Multiagent Justification Logic with Interacting Justifications -- A Framework for Epistemic Gossip Protocols -- Compliance Games -- Synthesis with Rational Environments -- STIT Based Deontic Logics for the Miners Puzzle -- Arbitrary Announcements on Topological Subset Spaces -- Theories in Practice and Real-World Problems Direct Exchange Mechanisms for Option Pricing -- A Study on the Influence of the Number of MTurkers on the Quality of the Aggregate Output -- Multi-Agent Cooperation for Optimizing Weight of Electrical Aircraft Harnesses -- Optimizing Emergency Medical Assistance Coordination in After-Hours Urgent Surgery Patients -- Spatial Coordination Games for Large-Scale Visualization -- Decision Making, Conflicts and Agreements Modeling a Multi-issue Negotiation Protocol for Agent Extensible Negotiations -- Conflict Resolution in Assumption-Based Frameworks -- Decision Making in Agent-Based Models -- Strategic Argumentation Under Grounded Semantics is NP-Complete -- Deliberative Argumentation for Service Provision in Smart Environments -- Priority-Based Merging Operator Without Distance Measures -- A Dialogical Model for Collaborative Decision Making Based on Compromises.
Keywords: Artificial intelligence; Computer simulation; Computer science; Computer software; Artificial Intelligence; Simulation and Modeling; Mathematical Logic and Formal Languages; Algorithm Analysis and Problem Complexity; Information Systems Applications (incl. Internet).